Transaction Costs, Portfolio Characteristics, and Mutual Fund Performance - Busse, Jeffrey A.; Chordia, Tarun; Jiang, Lei; Tang, Yuehua (Management Science, 2021)
We study the interdependencies between transaction costs, portfolio characteristics, and mutual fund performance. Using a novel data set of actual mutual fund trades, we find that, controlling for investment style, larger funds realize lower percentage transaction costs than smaller funds. Larger mutual funds trade less frequently and hold bigger stocks to actively avoid incurring higher trading costs. Gross returns of larger funds are lower than those of smaller funds due, in part, to the characteristics of their holdings, which suggests that decreasing returns to scale could arise due to limited investment opportunities because of trading cost constraints. Taken together, our results highlight the trade-offs faced by mutual funds between trading costs, portfolio characteristics, and fund performance as they grow in size. This paper was accepted by Karl Diether, finance.